Influence of exercise on serum brain-derived neurotrophic factor concentrations in healthy human subjects - Tang, Siu Wa; Chu, Emily; Hui, Tomy; Helmeste, Daiga; Law, Cindy (Neuroscience letters, 2008)
The effect of short-term exercise (15 min step-exercise) on serum brain-derived neurotrophic factor (BDNF) levels was evaluated in healthy human subjects. Results showed a short-term, significant increase in serum BDNF levels after exercise. Intra-individual differences in serum BDNF levels were remarkably small on the rest day and also when compared to rest values on the day of the exercise test. Inter-individual differences, on the other hand, were larger by comparison. The result of this study supports the need for larger sample size in studies on BDNF changes in psychiatric disorders or psychiatric drug effects.